Caching Strategies with Mobile Cloud Wireless Mesh: A Study in Disaster Risk and Resilience - Mercado, Neil Angelo M (Archīum Ateneo, 2021)
We present different caching approaches to an easily deployable; efficient; and resilient wireless mesh network of Mobile Cloud or Near Cloud System. Prepositioning this low-cost and low-powered caching terabyte caching system in everyday use i.e. in campuses; in Local Government Units; malls; and transport hubs doing their critical services; we anticipate its use in disaster scenarios. It is designed as an aid in disaster planning and preparedness and served as a relay of intelligent information and provided valuable contents to its users during and after disaster. As part of Ateneo Innovation Center's multiplatform resilient communication and information system; the Near Cloud system was deployed during university-wide emergency drill and in a real disaster scenario; proven successful for immediate disaster response; survivor and victim location; and saving lives. We propose the use of interactive digital signage in field operations to assist in search and reunification of families. Different use cases and deployments of the Near Cloud. This paper recognizes the importance of holistic and comprehensive disaster preparedness and risk reduction management especially in the context of a disaster-prone country like the Philippines.